Financial Development, Human Capital, and Investment in 7 ASEAN Countries: A Triangular Analysis of Economic Growth - Regina Safira Amaranti; Akhmad Syakir Kurnia (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
Economic growth is the main goal of all countries in the world, both developed and developing countries. Initially, growth theory only emphasized labor, capital, and natural resources, yet it often overlooked the contribution of financial systems. The financial sector will trigger economic growth through its intermediary function. The objective of this study is to see the influence of financial sector development, human capital, and investment in boosting economic growth in 7 ASEAN countries. This study employs secondary data, including gross domestic product (GDP), the ratio of broad money to GDP, the ratio of domestic credit to GDP, gross fixed capital formation, and the education index, utilizing a fixed effects model with the generalized least squares (GLS) approach as the analytical tool to estimate the regression model. The results of this study are that the ratio of broad money to GDP has a negative effect on economic growth in 7 ASEAN countries. Meanwhile, the ratio of credit to GDP, gross fixed capital formation, and the education index have a positive effect on economic growth in 7 ASEAN countries. We therefore contribute to the literature by adding the theory of economic growth, which subsequently impacts the real sector.